Developing Circular Motion Physics Module Integrated with Gumbaan Local Wisdom in Cooperative Learning Setting to Improving Learning Achievement - Saidatun Navisah; Mustika Wati; Abdul Salam M (Universitas Lambung Mangkurat, 2021)
This research is carried out to examine the developed circular motion physics module in a cooperative learning setting for students of Grade X Science Senior High School in Banjarmasin. This study's general objectives are to produce a circular motion physics module integrated with gumbaan local wisdom in cooperative learning settings and describe its feasibility. Moreover, this study's specific objectives aimed to describe the validity, practicality, and effectiveness of the module. This study utilizes the ADDIE (Analyze, Design, Develop, Implement, Evaluate) development design model. The instruments used consisted of module validation sheets, students’ questionnaire responses, and learning outcome test. The results of the study indicated that: (1) the validity of the module, based on the content and display, obtained a score of 3.20, which fell in the